Trends in incidence and 5‐year mortality in men with newly diagnosed, metastatic prostate cancer—A population‐based analysis of 2 national cohorts. Issue 14 (3rd May 2018) - Helgstrand, John T.; Røder, Martin A.; Klemann, Nina; Toft, Birgitte G.; Lichtensztajn, Daphne Y.; Brooks, James D.; Brasso, Klaus; Vainer, Ben; Iversen, Peter
Abstract : BACKGROUND: Early detection has increased prostate cancer (PCa) incidence. Randomized trials have demonstrated that early detection reduces the incidence of de novo metastatic PCa. Concurrently, life‐prolonging treatments have been introduced for patients with advanced PCa. On a populations‐based level, the authors analyzed whether early detection and improved treatments changed the incidence and 5‐year mortality of men with de novo metastatic PCa. METHODS: Men diagnosed with PCa during the periods 1980 to 2011 and 1995 to 2011 were identified in the US Surveillance, Epidemiology, and End Results (SEER) program and the Danish Prostate Cancer Registry (DaPCaR), respectively, and stratified according to period of diagnosis. Age‐standardized incidence rates were calculated. Five‐year mortality rates for de novo metastatic PCa were analyzed using competing risk analysis. RESULTS: Totals of 426, 266 and 47, 024 men were identified in SEER and DaPCaR, respectively. Of these, 29, 555 and 6874 had de novo metastatic PCa. The incidence of de novo metastatic PCa decreased (from 12.0 to 4.4 per 100, 000 men) in the SEER cohort (1980‐2011), whereas it increased (from 6.7 to 9.9 per 100, 000 men) in the DaPCaR cohort (1995‐2011). Five‐year PCa mortality in the SEER cohort was stable for men diagnosed with de novo metastatic PCa from 1980 to 1994 and increased slightly in the latest periods studied ( P < .0001), whereas it decreased by 16.6% ( P < .0001) in the DaPCaR cohort. CONCLUSIONS: Despite earlier detection, de novo metastatic PCa remains associated with a high risk of 5‐year disease‐specific mortality. The reduced 5‐year PCa mortality in the Danish cohort is largely explained by lead‐time. Early detection strategies do indeed decrease the incidence of de novo metastatic PCa, as observed in the SEER cohort. This achievement, however, must be weighed against the unsolved issue of overdetection and overtreatment of indolent PCa. Cancer 2018;124:2931‐8. © 2018 American Cancer Society . Abstract : Active early detection of prostate cancer indeed has a positive impact on both the incidence and survival of men with de novo metastatic disease at a population‐based level. However, this benefit must be weighed against the continuous problem of overdetection, and subsequent overtreatment, of indolent prostate cancer. See also pages 2890‐2.